The Correlation Between Fear Of Missing Out (FoMO) Phenomenon And Consumptive Behaviour In Millennials - Melinda Stefani Yaputri; Dindin Dimyati; Haris Herdiansyah (Eligible : Journal of Social Sciences, 2022)
Consumptive behaviour has changed as a frequent and normal act to be done as a result of globalization. Several previous research/studies have revealed that such consumption tendencies are influenced not just by brand quality and price, but also by psychological factors such as peer pressure. Due to the lack of communication barriers, an individual's tendency to follow others emerges as motivation. The goal of this research is to see if there is a correlation between the Fear of Missing Out (FoMO) phenomenon and consumer behaviour. This study employed a quantitative method with an explanatory research approach. The data was collected using online questionnaires sent to 125 millennials aged 20 to 38 years old, using a convenience sampling technique. With a Pearson correlation value of 0,970, this study found a positive and strong relationship between FoMO and Consumptive Behaviour.